"Dual-Key-and-Lock" dual drug carrier for dual mode imaging guided chemo-photothermal therapy. (1st October 2020) - Tian, Feng; Chi, Bin; Xu, Chen; Lin, Caixue; Xu, Zushun; Whittaker, Andrew K.; Zhang, Cheng; Li, Ling; Wang, Jing
Abstract : Drug resistance and side effects are the two main problems of chemotherapy. Abstract : Drug resistance and side effects are the two main problems of chemotherapy. In order to address these big challenges, p-PB@d-SiO2, which has the ability to co-deliver both the hydrophobic drug doxorubicin hydrochloride (DOX) and the hydrophilic drug ibuprofen (IBU), is constructed to achieve synergistic treatment. The drug-loaded nanoparticle consists of porous Prussian blue (p-PB) as the core and dendrimer-like SiO2 (d-SiO2 ) as the shell, which is further thiolated and coated with polyethylene glycol thiol (HS-PEG) to form the "Dual-Key-and-Lock" drug carrier p-PB@d-SiO2 -SS-PEG. The locked drugs can only be released in the presence of cooperative triggers, i.e., a high glutathione concentration (the first key) and an acidic environment (the second key). The "dual key"-triggered release is much more significant in cancer lesions than in normal tissues, reducing side effects. Furthermore, cell viability experiments highlight the superior therapeutic efficacy of the dual-drug-loaded nanoparticles compared with the single-drug systems (60%, 73% and 86% vs. 56%, 68%, and 76% at 100, 200 and 500 μg mL −1, respectively). In vitro and in vivo experiments demonstrate the potential application of p-PB@d-SiO2 -SS-PEG for dual-mode fluorescence and magnetic-resonance-imaging-guided chemo-photothermal therapy. The "Dual-Key-and-Lock" drug carrier system exhibits the "1 + 1 > 2" effect, demonstrating its excellent performance in synergy therapy for improved therapeutic efficiency and thereby reducing conventional drug resistance and side effects.